Hyper-reactive Malarial Splenomegaly (HMS) in a patient with β thalassaemia syndrome - Amoako, Yaw Ampem (Pan Afr Med J, 2014)
This report describes a case of hyper-reactive malarial splenomegaly in a patient with a thalassaemia syndrome. Increased haemoglobin A(2) is valuable for the diagnosis of common forms of β-thalassemia, while haemoglobin F (HbF) helps in diagnosis of the rarer δβ- forms. Thalassemia is characterised by splenomegaly and is common in malaria endemic areas. Hyper-reactive malarial splenomegaly is also a common cause of massive splenomegaly in malaria endemic areas. Splenic enlargement regresses with prolonged antimalarial therapy